The Implementation of Team-Based Learning for English Department Students - Ariani, Aura Zahro; Aviani, Cynthia Tri Puji (Universitas Lambung Mangkurat, 2023)
The purpose of this study is to explore English Education Department students’ perceptions and experiences about the implementation of Team-Based Learning for their class. The study was carried out using a qualitative methodology, and five students were used as the sample population for an interview. The total number of participants who took part in this study was 33 students who came from the second grade from semester 6. Participants were given a close-ended questionnaire to collect their perceptions about team-based learning. According to the survey, the majority of students believed that group projects enhanced learning, although some challenges persisted. As a consequence of the interview findings, it was discovered that several of the issues raised by the students were brought on by the group's members. Some students preferred working by themselves had varying levels of skill, found it challenging to speak with others, did not respect differing viewpoints, did not want to collaborate (students who study more slowly), and did not want to learn.